(5/2)t-1=3+(3/2)t

Simple and best practice solution for (5/2)t-1=3+(3/2)t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5/2)t-1=3+(3/2)t equation:



(5/2)t-1=3+(3/2)t
We move all terms to the left:
(5/2)t-1-(3+(3/2)t)=0
Domain of the equation: 2)t!=0
t!=0/1
t!=0
t∈R
Domain of the equation: 2)t)!=0
t!=0/1
t!=0
t∈R
We add all the numbers together, and all the variables
(+5/2)t-(3+(+3/2)t)-1=0
We multiply parentheses
5t^2-(3+(+3/2)t)-1=0
We multiply all the terms by the denominator
5t^2*2)t)-(3+(-1*2)t)+3=0
We add all the numbers together, and all the variables
5t^2*2)t)-(3+(-2)t)+3=0
Wy multiply elements
10t^3-2)t)+3=0
We do not support etpression: t^3

See similar equations:

| 8x-(3x-10)=34 | | 60x=0.15 | | 236784+x34876587648623+4943659+69=x | | -2(v+9)=4v-30 | | 4(z-5)+25=29 | | 16^1.25=x | | 2x+40x=74 | | 2(-4m+7)=-1-3m | | -7y+12=8(y+9) | | 2x+45=x+29 | | 18=-7(8k+2)-8(k+4) | | 2+6x=1–x | | 4r+1=12 | | 2x-6=7x-49 | | 2x(x+3)=x=23 | | -10k=-60 | | x-44-x3=6 | | 186t+16=1132 | | 240+0.25=180+0.40m | | 4d+14=3(d-1) | | 2(h+3.5)=-11 | | 4y9-2y3=10 | | 170+0.15x=267.50 | | 3x-3=6-(9x+9) | | 28x-1+146=22x-3 | | 2(y-1)+y=14 | | x+(1+4x)=106 | | Y/3+y=8 | | -16(d+1)=-20 | | x10+3x5=72 | | 9-3x-1=5x+2 | | 8x-17=4x+33 |

Equations solver categories